Enhancing the Creative Potential of Micro and Small Enterprises in Cianjur Regency - Nurjaman, Iman; Jaya, Hasbi Sukma (Universitas Djuanda, 2025)
The implementation of the 2024 Community Service Program by Suryakancana University, aligned with government initiatives, serves as a crucial effort in supporting national development by accelerating improvements in the Human Development Index (HDI). This community service, conducted in Girimukti Village, aims to enhance community welfare through the development of micro and small enterprises. Activities included assistance in product creation, packaging, and marketing. The program employed a descriptive method with a focus on building competitive advantages, specifically targeting the optimization of skills in processing cassava-based natural products. The results of the program demonstrated an increase in understanding among micro and small business actors, contributing positively to business development and promoting economic independence within the community. Additionally, a new cassava-based product—crispy tape balls—was successfully developed, complete with improved packaging and a simple yet elegant logo, thereby enhancing the product's market value.